Waltz with Bashir [videorecording (DVD)] - Folman, Ari; Sivan, Ori, 1963-; Frenkel, Shmuel (Sony Pictures Home Entertainment, 2009)
After not being able to recall the time he spent on an Israeli Army mission during the Lebanon War, Ari attempts to unravel the mystery by traveling around the world to interview old friends and comrades. As the pieces of the puzzle begin to come together, his memory begins to return in illustrations that are surreal.